2014
DOI: 10.1111/ijpp.12104
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of secondary prevention of stroke: a qualitative study of stroke patients’ beliefs, concerns and difficulties with their medicines†

Abstract: Many of the difficulties stroke patients have adhering to secondary prevention strategies are potentially preventable with tailored information provision and appropriate monitoring and follow-up by primary healthcare professionals. We have designed an intervention addressing the identified barriers to medicine taking, the impact of which is currently being measured in a randomised controlled trial of a pharmacist-led home-based clinical medication review in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…11,17 Also, patient factors, such as vulnerability, 18 the presence of comorbidities, 19 drug interactions, and/or side-effects, 20 may lead doctors to decide not to treat older patients. In addition, older patients themselves may fail to attend followup consultations, or stop taking medication because of illness perceptions 21,22 or sideeffects. Besides these individual factors, the organisation of health care also may influence treatment uptake.…”
Section: Introductionmentioning
confidence: 99%
“…11,17 Also, patient factors, such as vulnerability, 18 the presence of comorbidities, 19 drug interactions, and/or side-effects, 20 may lead doctors to decide not to treat older patients. In addition, older patients themselves may fail to attend followup consultations, or stop taking medication because of illness perceptions 21,22 or sideeffects. Besides these individual factors, the organisation of health care also may influence treatment uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Randomisation to intervention or usual care group was undertaken using sequentially numbered opaque envelopes prepared by an independent person to ensure allocation concealment. Previous work suggests patients living alone have more problems with their medicines 3. Therefore, stratification was applied prior to randomisation to ensure equal numbers of living alone in each group.…”
Section: Methodsmentioning
confidence: 99%
“…In the acute setting, this usually includes a specialist clinical pharmacist, while, on discharge from hospital, pharmaceutical care is generally managed by non-specialist community pharmacists. A proportion of patients with stroke on discharge do not have contact with the community pharmacist because they are unable to visit the pharmacy in person 3 4. Qualitative studies in homes of patients with stroke have identified the barriers and difficulties which patients experience when taking their medicines 3 4.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations